2022
DOI: 10.24815/jpsi.v10i2.24114
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Peran Hands on Activity dalam Model Predict Observe Discuss Explain Terhadap Pemahaman Konsep Sains SD

Abstract: Learning science by rote can lead to misunderstandings or misconceptions. Misunderstanding of concept understanding must be avoided by students, so that the knowledge process in obtaining conceptual information is meaningful for students. This study aims to determine the role of the PODE Hands on Activity model in understanding science concepts for fourth grade elementary school students. This research uses a quantitative approach with a quasi experimental design type of research in the form of nonequivalent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Implementation of learning by providing problems can improve students' understanding of concepts (Fitriani et al, 2016). Herdianto et al (2022) also found the results that the implementation of learning based on student activities could increase understanding of concepts.…”
Section: Table 3 N-gain Score Groupsmentioning
confidence: 90%
“…Implementation of learning by providing problems can improve students' understanding of concepts (Fitriani et al, 2016). Herdianto et al (2022) also found the results that the implementation of learning based on student activities could increase understanding of concepts.…”
Section: Table 3 N-gain Score Groupsmentioning
confidence: 90%